Sulfonated tryptanthrin anolyte increases performance in pH neutral aqueous redox flow batteries - Daniela Pinheiro (Nature Portfolio, 2021)
Redox flow batteries working at a neutral pH combine high stability and environmental safety, but their power output is still limited. Here, the authors present an aqueous, all-organic redox flow battery, with sulfonated tryptanthrin as an anolyte solution, reaching a cell voltage of 0.94 V.